Public Administration, Habermas and the Crisis of Legitimacy in the Youth Justice System: An Australian Case Study. Issue 4 (1st October 2020) - Bessant, Judith; Watts, Rob
Abstract : Using an Australian case in which a liberal-democratic state systematically breached the human rights of children involved in in its youth justice system, this article explores the idea of 'legitimacy' and 'legitimation crisis' in the modern administrative state. We acknowledge the relevance of Habermas' account of a crisis of legitimacy when responding to Carl Schmitt's challenge to the claim to legitimacy vested in liberal rule of law principles found in Schmitt's account of state sovereignty and the power to declare exceptions. In this way we highlight some issues with how conventional public administration studies have taken the liberal framework and principles like the rule of law and equality of all before the law for granted. We argue that this field of study has paid too little attention to the role of sovereign power evident when the executive creates what Dyzenhaus and Vermeules refer to as legal 'black and gray holes'. This highlights the value of reconsidering the concern by mainstream public administration research and theory with questions of administrative discretion and the need to pay much more attention to the role of the executive in the administration of systems like the justice system.